Alkaloids, styryl lactones, and acetogenin from the roots of Goniothalamus lanceolatus Miq. and their antiproliferative activity / Nurulfazlina Edayah Rasol - Rasol, Nurulfazlina Edayah (2020)
Goniothalamus lanceolatus Miq., locally known as selukai or getimang is an ethnomedicinal plant indigenous to Sarawak. It is used traditionally to treat cancer. Phytochemical investigation on the roots of G. lanceolatus Miq. was conducted with the objective of comprehensively analyse the chemical constituents present in the roots of G lanceolatus, especially the ones potentially active as antiproliferative agents. The roots of G lanceolatus Miq. was extracted successively using hexane, dichloromethane, and methanol. The hexane and dichloromethane extracts showed antiproliferative activity against colorectal and lung cancer cell lines with percentage viability of cell less than 15%. Among the two extracts, the HPLC-DAD profile of the dichloromethane extract revealed the presence of more active UV components, and thus selected for further investigation. Mass-based dereplication strategy using inhouse and online mass database system successfully identified 24 constituents comprising of styryl lactones, alkaloids, and acetogenins in the dichloromethane extract. Isolation and purification from the active antiproliferative fractions, M2 to M7 led to characterization often styryl lactones, five alkaloids, and one acetogenin, where six dereplicated compounds were verified. All the structures were elucidated using 1Dand 2D-NMR spectroscopy. Absolute configurations of the styryl lactones were established by ECD analysis through comparison of the experimental and theoretically calculated ECD spectra, while stereochemistry of the alkaloids were established using the single X-ray crystallography data. The known 5-goniothalamin and parvistone D, are reported for the first time from Goniothalamus genus. Two new styryl lactones 57?,6i?-5-hydroxy-6-styryltetrahydropyrane-2-one and goniolanceolatin E, and five new styryl lactone diastereomers, 5i?,6i?-5-acetylgoniothalamin, 5R,6R-5- hydroxygoniothalamin, goniofupyrone B, deoxygoniopypyrone B, and goniolanceolatin A, along with a known pyrano-pyrone, lS,5S,7R,8S,3-exo,7-endo- (+)-8-ep/-9-deoxygoniopypyrone are described. The 6S/IS- styryl lactones isolated in this work are new discoveries in Goniothalamus species. Biogenesis pathway of these 6S/IS styryl lactones are proposed. In addition, two new alkaloids, (-)- goniolanceolactam and 2-acetyl-3-amino-1,4-naphthoquinone were also identified along with the known alkaloids, 2-acetyl-3-amino-5-hydroxy-1,4-naphthoquinone, cleistopholine and liriodenine, and the acetogenin, annonacin. 5-Goniothalamin, (-)- goniolanceolactam and annonacin exhibited potential antiproliferative activity against all tested cancer cell lines with the IC50 values of less than 10.0 |uM. The alkaloids, 2- acetyl-3 -amino-1,4-naphthoquinone and 2-acetyl-3 -amino-5-hydroxy-1,4- naphthoquinone, as well as liriodenine demonstrated antiproliferative against HCT116, A549, and NCI-H23 cell lines with IC50 values ranging between 4.5 to 10.3 |uM. 5i?,6i?- 5-hydroxygoniothalamin showed selective activity against lung cancer cell lines, A549, and NCI-H1299, with the IC50 values of 8.0 and 8.9 \*M, respectively. Other styryl lactones exhibited only weak activity. All isolated compounds were non-toxic to normal cell lines except for annonacin.